ANALYSIS OF BUSINESS ENVIRONMENT AND BARRIERS - Mitar Perušić; Miladin Gligorić; Radislav Filipović (Journal of Engineering & Processing Management, 2013)
This paper presents the results of tests perception of business environment and barriers to business by attitudes of entrepreneurs in local communities. It is well known that general region of the Balkan countries, is faced with the problem of the lack of investment as well as domestic and foreign direct investment. One of the major causes of course, are important obstacles in business that affect the negative perception of the business environment in the region. For this reason, there are a number of activities organized by local communities but also higher levels of government in order to implement the entire projects as well as measures to create a favorable business frinedly environment and create of the competitive area of business in relation to the neighboring countries.
Keywords: Barriers; business environment; local community